Spin-on carbon hard mask composition having high planarization performance and patterning method using the same
Patent Information
- Application Number
- JP2024556748
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-06
- Filing Date
- 2023-02-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-02-27
Smart Images

Figure 2025510849000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hard mask composition that maintains high planarization properties useful for semiconductor lithography processes, and more particularly to a spin-on carbon hard mask composition having high planarization performance, which comprises a 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthene]3-one polymer, an organic solvent, and a surfactant, and has a thickness of 4,010 Å or less and a planarization degree of 20% or less, and a patterning method using the same. [Background technology]
[0002] The miniaturization and integration of devices has necessitated the realization of finer patterns in semiconductor processes. As a method for forming such fine patterns, research and development is underway on methods such as developing exposure equipment or finer photoresist patterns by introducing additional processes. Furthermore, photoresists and photolithography process tools with higher resolution are being developed to increase the integration density of semiconductor devices and enable the formation of finer structures having dimensions in the nanometer range. In the past, semiconductor manufacturing processes used an i-line light source with a wavelength of 365 nm to form patterns on semiconductor substrates, but to form finer patterns, a light source with an even smaller wavelength band was required. Recent technological trends include the ongoing development of lithography technologies using light sources such as KrF (248 nm), ArF (198 nm), and EUV (extreme ultra violet, 13.5 nm). These technologies are either currently commercialized or in the process of being commercialized. Current technology requires fine patterns, but the thickness of photoresist is gradually becoming thinner to realize fine patterns, resulting in the phenomenon of photoresist pattern collapse. It is no longer possible to etch the layer to be etched using the thinner photoresist pattern. To improve this, a hard mask, which has excellent etching properties, is introduced between the photoresist layer and the layer to be etched. The hard mask process refers to a process of etching and patterning a hard mask using a photoresist pattern, and then etching the layer to be etched using the hard mask pattern. The hard mask film is manufactured using a chemical vapor deposition (CVD) method or a spin on coating method. Hard mask films manufactured by the CVD method have drawbacks such as increased initial costs due to the use of an evaporator, increased process time, particle issues, etc. To overcome these drawbacks, the spin-on coating method was developed. The spin-on coating method is a technology that reduces costs and process time by using materials that can be spin-coated. It has the advantages of lower initial investment costs compared to the CVD method, uniform coating properties, easy control of coating thickness, and reduced process time. In the case of spin-on hardmasks, there has been a demand for new technologies and developments related to further miniaturization and pattern stacking in semiconductor processes, and there is a demand for the development of new hardmask films for materials and technologies for uniformly coating a hardmask film on a wafer having fine patterns. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Korean Patent No. 10-0874655 [Patent Document 2] Korean Patent No. 10-1230529 [Patent Document 3] Korean Patent No. 10-1721979 [Patent Document 4] Korean Patent No. 10-1777687 [Patent Document 5] Korean Patent No. 10-2240213 Summary of the Invention [Problem to be solved by the invention]
[0004] The object of the present invention is to provide a patterning method and composition using a spin-on carbon hard mask in a semiconductor manufacturing process, which not only has a low refractive index and extinction coefficient and excellent etching resistance against dry etching, but also is uniformly coated to provide good coating performance and achieve high planarization performance, and to provide a patterning method using the composition. [Means for solving the problem]
[0005] The present invention provides a spin-on hard mask composition having high planarization properties, characterized in that the composition has a 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthen]-3-one derivative polymer represented by the following chemical formula 1, or a structure containing the same, and the weight-average molecular weight of the derivative polymer is 1,000 to 5,000, the thickness is 4,000 Å or less, and the degree of planarization is 20% or less. [ka] In the formula, l, m, and n are in the ranges of 1≦l≦20, 1≦m≦40, and 1≦n≦20, respectively; R1 is hydrogen (H), a hydroxyl group (OH), a ketone group (CO), an ether group (COC), an aldehyde group (CHO), [ka] [ka] [ka] [ka] R2 includes any one of [ka] [ka] [ka] [ka] [ka] [ka] [ka] R3 is hydrogen (H), a hydroxyl group (OH), [ka] [ka] [ka] [ka] [ka] Includes any of the following: In the formula, the ratios of R1, R2, and R3 are mainly used to form polymers with different ratios to improve the high planarization performance of the entire polymer structure and to improve the thermal curing reactivity and etch selectivity. In the formula, R1 is a 3',6'-dihydroxy-3H-spiro[2-benzofuran]-1,9'-xanthen]-3-one derivative, which has a high flatness performance improving effect. In the formula, R2 is mainly composed of an acid catalyst, and the polymer material formed has a high planarization performance improving effect and solubility in organic solvents. In the formula, R3 mainly has the effect of enhancing the thermosetting reactivity and etch resistance of the entire polymer structure. When the weight average molecular weight of the polymer represented by Chemical Formula 1 is less than 1,000, a sufficient amount of polymer structure is not generated, resulting in poor etch resistance, and when it exceeds 5,000, the physical properties of the coated surface may be non-uniform. The hard mask composition may include 1 wt % to 50 wt % of the polymer represented by Chemical Formula 1, 50 wt % to 98 wt % of an organic solvent, and more than 0 to 2 wt % of a surfactant. If the polymer component is less than 1 wt % or more than 50 wt %, the coating thickness may be less than or more than the target coating thickness, making it difficult to achieve an accurate coating thickness, and if a coating thickness greater than the target is required, the coatability may be poor. The organic solvent may be one selected from the group consisting of propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), cyclohexanone (CHN), cyclopentanone (CPN), γ-butyrolactone (GBL), ethyl lactate (EL), methyl ethyl ketone (MEK), n-butyl acetate, N-methylpyrrolidone (NMP), methyl 3-methoxypropionate (MMP), and ethyl 3-ethoxypropionate (EEP), or a mixture of two or more of these. The surfactant may be one selected from the group consisting of ionic and nonionic surfactants such as polyacrylates, polyfluorocarbons, polysiloxanes, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene nonyl phenyl ethers, polyoxyethylene octyl phenyl ethers, polyoxyethylene polyoxypropylenes, polyoxyethylene lauryl ethers, and polyoxyethylene sorbitans, or a mixture of two or more thereof. According to another embodiment of the present invention, there is provided a patterning method, comprising applying the composition onto a layer to be etched by spin coating, and then performing a baking process to form a hard mask layer. The thickness of the spin coating of the composition is not particularly limited, but may be from 100 Å to 20,000 Å. The baking process may be performed at a temperature of 150° C. to 400° C. for 1 to 5 minutes to cause a self-crosslinking reaction. Effect of the Invention
[0006] The spin-on carbon hard mask composition having high planarization performance and the patterning method using the composition according to the present invention have good coating performance by being uniformly coated at a thickness of 4,010 Å or less, provide a flat coating layer with a planarization degree of 20% or less, and realize high planarization performance. In addition, since the composition has a low refractive index and absorptivity, a high etch selectivity, and sufficient resistance to multiple etch, it shows an effect of providing excellent performance when forming semiconductor fine patterns. [Brief description of the drawings]
[0007] [Figure 1] 13 shows FE-SEM data related to the planarization properties of the polymer provided in Experimental Example 5. [Diagram 2] FIG. 11 is a diagram relating to a formula for calculating the degree of flattening in the flattening characteristic. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The carbon hard mask composition according to the present invention will be described in detail below. The present invention provides a spin-on hard mask composition having high planarization properties, characterized in that the composition comprises a 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthen]-3-one derivative polymer represented by the following chemical formula 1, or a structure containing the same, the weight average molecular weight of the derivative polymer being 1,000 to 5,000, preferably 1,000 to 4,000, and more preferably 1,500 to 3,000, the thickness being 4,010 Å or less, and the degree of planarization being 20% or less. [ka] In the formula, l, m, and n are in the ranges of 1≦l≦20, 1≦m≦40, and 1≦n≦20, respectively; R1 is hydrogen (H), a hydroxyl group (OH), a ketone group (CO), an ether group (COC), an aldehyde group (CHO), [ka] [ka] [ka] [ka] R2 includes any one of [ka] [ka] [ka] [ka] [ka] [ka] [ka] R3 is hydrogen (H), a hydroxyl group (OH), [ka] [ka] [ka] [ka] [ka] Includes any of the following: In the formula, the ratios of R1, R2, and R3 are mainly used to form polymers with different ratios to improve the high planarization performance of the entire polymer structure and to improve the thermal curing reactivity and etch selectivity. In the formula, R1 is a 3',6'-dihydroxy-3H-spiro[2-benzofuran]-1,9'-xanthen]-3-one derivative, which has a high flatness performance improving effect. In the formula, R2 is mainly composed of an acid catalyst, and the polymer material formed has a high planarization performance improving effect and solubility in organic solvents. In the formula, R3 mainly has the effect of enhancing the thermosetting reactivity and etch resistance of the entire polymer structure. When the weight average molecular weight of the polymer represented by Chemical Formula 1 is less than 1,000, a sufficient amount of polymer structure is not generated, resulting in poor etch resistance, and when it exceeds 5,000, the physical properties of the coated surface may be non-uniform.
[0009] The hard mask composition may include 1 wt % to 50 wt % of the polymer represented by Formula 1, 50 wt % to 98 wt % of an organic solvent, and more than 0 wt % to 2 wt % of a surfactant. If the polymer component is less than 1 wt % or more than 50 wt %, the coating thickness may be less than or more than the target coating thickness, making it difficult to achieve an accurate coating thickness, and if a coating thickness greater than the target is required, the coatability may be poor. The organic solvent may be one selected from the group consisting of propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), cyclohexanone (CHN), cyclopentanone (CPN), γ-butyrolactone (GBL), ethyl lactate (EL), methyl ethyl ketone (MEK), n-butyl acetate, N-methylpyrrolidone (NMP), methyl 3-methoxypropionate (MMP), and ethyl 3-ethoxypropionate (EEP), or a mixture of two or more of these. The surfactant may be one selected from the group consisting of ionic and nonionic surfactants such as polyacrylates, polyfluorocarbons, polysiloxanes, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene nonyl phenyl ethers, polyoxyethylene octyl phenyl ethers, polyoxyethylene polyoxypropylenes, polyoxyethylene lauryl ethers, and polyoxyethylene sorbitans, or a mixture of two or more thereof. According to another embodiment of the present invention, there is provided a patterning method, comprising applying the composition onto a layer to be etched by spin coating, and then performing a baking process to form a hard mask layer. The thickness of the spin coating of the composition is not particularly limited, but may be from 100 Å to 20,000 Å. The baking process may be performed at a temperature of 150° C. to 400° C. for 1 to 5 minutes to cause a self-crosslinking reaction. Preferred examples of the present invention and comparative examples will be described below. However, the following examples are merely preferred examples of the present invention, and the present invention is not limited to the following examples.
[0010] Example 1 [ka] 15.0g (0.045mol) of 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthene]-3-one, 15.0g (0.090mol) of 1,4-bismethoxymethylbenzene, 20.3g (0.045mol) of 9,9-bis(6-hydroxy-2-naphthyl)florine, and 150g of propylene glycol monomethyl ether acetate were placed in a four-neck flask, and then a nitrogen atmosphere was created. 0.07g (0.00045mol) of diethyl sulfate was placed in the reactor as an initiator, and refluxed while heating at 140°C for 9 hours. After the reaction was completed, the solution was purified with an ethanol / water (9:1) solution, recrystallized with an ethanol / distilled water (9:1) solution, and then vacuum dried to obtain a polymer compound having a weight average molecular weight (Mw) of 1,500 based on standard polystyrene as a result of GPC measurement. Example 2 Except for changing the reaction time to 15 hours, the synthesis was carried out in the same manner as in Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated in terms of standard polystyrene was 3,000. Example 3 [ka] 15.0g (0.045mol) of 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthene]-3-one, 21.7g (0.090mol) of 4,4'-bis(methoxymethyl)-1,1'-biphenyl, 20.3g (0.045mol) of 9,9-bis(6-hydroxy-2-naphthyl)florine, and 150g of propylene glycol monomethyl ether acetate were placed in a four-neck flask, and a nitrogen atmosphere was created. 0.07g (0.00045mol) of diethyl sulfate was placed in the reactor as an initiator, and refluxed at 140℃ for 9 hours. After the reaction was completed, the solution was purified with an ethanol / water (9:1) solution, recrystallized with an ethanol / distilled water (9:1) solution, and then vacuum dried to obtain a polymer compound having a weight average molecular weight (Mw) of 1500 calculated as standard polystyrene according to GPC measurement results. Example 4 Except for changing the reaction time to 15 hours, the synthesis was carried out in the same manner as in Example 3. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated as standard polystyrene was 3,000. Example 5 [ka] 15.0g (0.045mol) of 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthene]-3-one, 23.1g (0.090mol) of 4,4'-bis(methoxymethyl)diphenyl ether, 20.3g (0.045mol) of 9,9-bis(6-hydroxy-2-naphthyl)florine, and 150g of propylene glycol monomethyl ether acetate were placed in a four-neck flask, and a nitrogen atmosphere was created. 0.07g (0.00045mol) of diethyl sulfate was placed in the reactor as an initiator, and refluxed at 140℃ for 9 hours. After the reaction was completed, the solution was purified with an ethanol / water (9:1) solution, recrystallized with an ethanol / distilled water (9:1) solution, and then vacuum dried to obtain a polymer compound having a weight average molecular weight (Mw) of 1500 calculated as standard polystyrene as a result of GPC measurement.
[0011] Example 6 Except for changing the reaction time to 15 hours, the synthesis was carried out in the same manner as in Example 5. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated as standard polystyrene was 3,000. Example 7 [ka] 18.3g (0.045mol) of 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthene]-3-one, 15.0g (0.090mol) of 1,4-bismethoxymethylbenzene, 20.3g (0.045mol) of 9,9-bis(6-hydroxy-2-naphthyl)florine, and 150g of propylene glycol monomethyl ether acetate were placed in a four-neck flask, and then a nitrogen atmosphere was created. 0.07g (0.00045mol) of diethyl sulfate was placed in the reactor as an initiator, and refluxed while heating at 140°C for 9 hours. After the reaction was completed, the solution was purified with an ethanol / water (9:1) solution, recrystallized with an ethanol / water (9:1) solution, and then vacuum dried to obtain a polymer compound having a weight average molecular weight (Mw) of 1,500 based on standard polystyrene as a result of GPC measurement. Example 8 Except for changing the reaction time to 15 hours, the synthesis was carried out in the same manner as in Example 7. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) in terms of standard polystyrene was 3,000. Example 9 [ka] 18.3g (0.045mol) of 3',6'-dihydroxy-3H-spiro[2-benzofuran(5-phenyl)-1,9'-xanthene]-3-one, 21.7g (0.090mol) of 4,4'-bis(methoxymethyl)-1,1'-biphenyl, 20.3g (0.045mol) of 9,9-bis(6-hydroxy-2-naphthyl)florine, and 150g of propylene glycol monomethyl ether acetate were placed in a four-neck flask, and a nitrogen atmosphere was created. 0.07g (0.00045mol) of diethyl sulfate was placed in the reactor as an initiator, and refluxed at 140℃ for 9 hours. After the reaction was completed, the solution was purified with an ethanol / water (9:1) solution, recrystallized using an ethanol / water (9:1) solution, and then vacuum dried to obtain a polymer compound having a weight average molecular weight (Mw) of 1,500 calculated as standard polystyrene, as determined by GPC measurement.
[0012] Example 10 Except for changing the reaction time to 15 hours, the synthesis was carried out in the same manner as in Example 9. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) in terms of standard polystyrene was 3,000. Example 11 [ka] 18.3g (0.045mol) of 3',6'-dihydroxy-3H-spiro[2-benzofuran(5-phenyl)-1,9'-xanthene]-3-one, 23.1g (0.090mol) of 4,4'-bis(methoxymethyl)diphenyl ether, 20.3g (0.045mol) of 9,9-bis(6-hydroxy-2-naphthyl)florine, and 150g of propylene glycol monomethyl ether acetate were placed in a four-neck flask, and a nitrogen atmosphere was created. 0.07g (0.00045mol) of diethyl sulfate was placed in the reactor as an initiator, and refluxed at 140℃ for 9 hours. After the reaction was completed, the solution was purified with an ethanol / water (9:1) solution, recrystallized using an ethanol / water (9:1) solution, and then vacuum dried to obtain a polymer compound having a weight average molecular weight (Mw) of 1,500 calculated as standard polystyrene, as determined by GPC measurement. Example 12 Except for changing the reaction time to 15 hours, the synthesis was carried out in the same manner as in Example 11. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) in terms of standard polystyrene was 3,000.
[0013] Comparative Example 1 [ka] 20g (1mol) of 9,9-bis(4-hydroxyphenyl) fluorine, 9.5g (1mol) of 1,4-bismethoxymethylbenzene and 150g of propylene glycol monomethyl ether acetate were placed in a four-neck flask, and then a nitrogen atmosphere was created. 0.07g (0.01mol) of diethyl sulfate was placed in the reactor as an initiator, and refluxed at 140°C for 10 hours. A compound with a weight average molecular weight (Mw) of 1,500 calculated based on standard polystyrene was obtained by purifying the product in the same manner as in Example 1. Comparative Example 2 Except for changing the reaction time to 14 hours, synthesis and purification were carried out in the same manner as in Comparative Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated as standard polystyrene was 4,000. Comparative Example 3 Except for changing the reaction time to 16 hours, synthesis and purification were carried out in the same manner as in Comparative Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated as standard polystyrene was 5,000. Experimental Example 1 3.0 g of the polymer compound obtained in Example 1, 13.6 g of propylene glycol monomethyl ether acetate, and 3.4 g of cyclohexanone were added and dissolved by stirring for 24 hours. The dissolved solution was filtered through a 0.2 μm fine filter to prepare a composition for forming a hard mask film. The prepared solution was coated on a silicon wafer using a spin coater. The wafer coated with the solution was heated on a hot plate at 240° C. for 1 minute and then continuously at 400° C. for 1 minute to form a hard mask film. Experimental Example 2 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 2 was used. Experimental Example 3 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 3 was used. Experimental Example 4 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 4 was used. Experimental Example 5 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 5 was used. Experimental Example 6 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 6 was used. Experimental Example 7 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 7 was used. Experimental Example 8 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Example 8 was used. Experimental Example 9 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Example 9 was used. Experimental Example 10 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Example 10 was used. Experimental Example 11 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Example 11 was used. Experimental Example 12 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Example 12 was used.
[0014] Comparative Experiment Example 1 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Comparative Example 1 was used. Comparative Experiment Example 2 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Comparative Example 2 was used. Comparative Experiment Example 3 The experiment was conducted in the same manner as in Experimental Example 1, except that 3.0 g of the polymer compound obtained in Comparative Example 3 was used. <Gap-Fill Property Evaluation> The solutions prepared in Experimental Examples 1 to 12 and Comparative Experimental Examples 1 to 3 were coated on a pattern wafer using a spin coater. The cross-section of the wafer was measured to check for the presence of voids. The experiment was repeated 5 times using each sample. The cross-section was confirmed using a scanning electron microscope (FE-SEM, manufactured by Hitachi, Ltd.) as the measurement equipment, and the measurement results are shown in Table 1.
Table 1
number
[0015] [Table 2] The results of the evaluation of the planarization characteristics of the hard mask film are shown in Table 2. According to the evaluation results, it was confirmed that Experimental Examples 1, 3 to 7, and 9 to 12 exhibited better planarization performance than Comparative Experimental Example 1. In contrast, Experimental Example 2, Experimental Example 8, Comparative Experimental Example 2, and Comparative Experimental Example 3 did not undergo planarization evaluation due to the presence of voids. The planarization degree of the hard mask film can be defined as excellent if the planarization degree is 20% or less compared to the coating thickness. Experimental Examples 1, 3 to 7, and 9 to 12 exhibited excellent planarization performance, and Experimental Example 5 was evaluated to have the best planarization degree of 9.2%. <Coating thickness characteristic test> The thickness of the hard mask films formed in Experimental Examples 1 to 12 and Comparative Experimental Examples 1 to 3 was measured, and the results are shown in Table 3. The equipment used was an Ellipsometer (manufactured by Horiba, Ltd.).
[0016] [Table 3] As a result of coating using the materials of the experimental and comparative experimental examples, the coating performance of Comparative Experimental Example 3 was evaluated as poor because the coating was not uniform on the surface of the wafer and the physical properties of the coating surface were non-uniform. <Measurement of weight average molecular weight> The weight average molecular weight obtained in the above examples was analyzed by gel permeation chromatography (GPC). The column used in the analysis was a product of Shodex Corporation, and the measurement conditions were as follows. Column temperature: 40° C., mobile phase: tetrahydrofuran (THF), flow rate: 1 mL / 1 min, GPC column: KF-801, 802, 803 (Shodex, 8×300 mm) were used. The results are shown in Table 4. [Table 4] <Optical property testing> The refractive index n and extinction coefficient k of the hard mask films formed in Experimental Examples 1 to 12 and Comparative Experimental Examples 1 to 3 were measured, and the results are shown in Table 5. The equipment used was an Ellipsometer (manufactured by Horiba, Ltd.).
[0017] [Table 5] The refractive index (n@193 nm) and absorption coefficient (k@193 nm) of the hard mask film were measured as shown in Table 5, except for Comparative Example 3, which was not evaluated due to poor coating properties. The refractive index (n@193 nm) of the hard mask film can be evaluated as excellent if it is 1.41 or less, and the absorption coefficient (k@193 nm) of the hard mask film can be evaluated as excellent if it is 0.50 or less. In the case of Experimental Examples 1 to 12, it was confirmed that the refractive index was 1.41 or less and the absorption coefficient was 0.50 or less, which was superior, as compared with Comparative Experimental Example 1 and Comparative Experimental Example 2. Among these, Experimental Example 3 showed the most excellent results, with a refractive index of 1.36 and an absorption coefficient of 0.46.
[0018] <Dry etch characteristic evaluation> The hard mask films formed in Experimental Examples 1 to 12 and Comparative Experimental Examples 1 and 2 were dry etched for 20 seconds using CF4 gas on dry etching equipment. The dry etch rate was quantified using the following Equations 2 and 3. The dry etch characteristics indicate the dry etch rate of the hard mask film when the ACL (amorphous carbon layer) is taken as 100%. When measuring the film thickness, a scanning electron microscope (FE-SEM, Hitachi) was used to check the cross section, and the measurement results are shown in Table 6, excluding Comparative Experimental Example 3, which was not evaluated due to poor coating properties.
number
number
[0019] Although the specific parts of the present invention have been described in detail above, it is clear to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the present invention. Therefore, the substantial scope of the present invention should be defined by the claims and their equivalents.
Claims
1. A spin-on hard mask composition having high planarization properties, comprising a 3',6'-dihydroxy-3H-spiro[2-benzofuran-1,9'-xanthene]-3-one derivative polymer represented by the following formula 1, an organic solvent, and a surfactant: 【Chemistry 1】 (In the formula, l, m, and n are in the ranges of 1≦l≦20, 1≦m≦40, and 1≦n≦20, respectively; R 1 represents hydrogen (H), hydroxyl group (OH), ketone group (CO), ether group (COC), aldehyde group (CHO), 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 R 2 teeth, 【Chemistry 6】 【Chemistry 7】 【Chemistry 8】 【Chemistry 9】 【Chemistry 10】 【Chemistry 11】 【Chemistry 12】 R 3 represents hydrogen (H), a hydroxyl group (OH), 【Chemistry 13】 【Chemistry 14】 【Chemistry 15】 【Chemistry 16】 【Chemistry 17】 (including any of the following)
2. 2. The spin-on hard mask composition having high planarization properties according to claim 1, wherein the hard mask composition includes a polymer having a weight average molecular weight of 1,000 to 5,000, and has a planarization degree of 20% or less at a thickness of 4,000 Å or less.
3. 3. The spin-on hard mask composition having high planarization properties as set forth in claim 2, wherein the weight average molecular weight of the polymer is 1,000 to 4,000.
4. 4. The spin-on hard mask composition having high planarization properties as set forth in claim 3, wherein the weight average molecular weight of the polymer is 1,500 to 3,000.
5. 2. The spin-on hard mask composition having high planarization characteristics according to claim 1, comprising 1 to 50 wt % of a polymer, 0 to 2 wt % of a surfactant, and 50 to 99 wt % of an organic solvent, based on the total composition.
6. 2. The spin-on hard mask composition having high planarization properties according to claim 1, wherein the organic solvent is selected from the group consisting of propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), cyclohexanone (CHN), cyclopentanone (CPN), γ-butyrolactone (GBL), ethyl lactate (EL), methyl ethyl ketone (MEK), n-butyl acetate, N-methylpyrrolidone (NMP), methyl 3-methoxypropionate (MMP), and ethyl 3-ethoxypropionate (EEP), or a mixture of two or more thereof.
7. 2. The spin-on hard mask composition having high planarization characteristics according to claim 1, wherein the surfactant is selected from the group consisting of one or a mixture of two or more selected from the group consisting of polyacrylates, polyfluorocarbons, polysiloxanes, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene nonyl phenyl ethers, polyoxyethylene octyl phenyl ethers, polyoxyethylene polyoxypropylenes, polyoxyethylene lauryl ethers, and polyoxyethylene sorbitans.
8. A patterning method comprising the steps of: applying the spin-on hard mask composition having high planarization properties according to any one of claims 1 to 7 onto a layer to be etched by spin coating; and performing a baking step to form a hard mask layer.
9. 9. The method of claim 8, wherein the baking process is performed at a temperature of 150° C. to 400° C. for 1 minute to 5 minutes to form a hard mask layer.
Citation Information
Patent Citations
New photoacid generator, resist material using the same, and pattern forming method
JP2009269953A
Positive resist material and patterning process
JP2013068928A
Underlayer film material and pattern forming method
JP2015018223A
Lithographic printing original plate, method for manufacturing lithographic printing plate, and printing method
JP2018140618A
Resist underlayer film material, pattern forming method, and resist underlayer film forming method
JP2018173520A